Evaluating Socio-Economic Impacts of Productive Zakat on Mustahik Empowerment: A Propensity Score Matching Analysis - Toni, Hariya; Syafii, Muhammad Hisyam; Bustami, Bustami; Azhari, Husain; Alaldaya, Rudyn (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2026)
This study assesses the socio-economic effects of productive zakat initiatives on mustahik empowerment in Indonesia through a quasi-experimental methodology employing Propensity Score Matching (PSM). Data from 160 participants across various Zakat Management Organizations were gathered April 2025. The study utilized a multifaceted empowerment paradigm encompassing economic, social, human capital, and psychological components to address gaps in Islamic social finance literature. Results indicate significant empowerment enhancements, evidenced by a 63.1% increase in the composite empowerment index (effect size d=2.29). Economic empowerment showed substantial benefits (72.7% rise, d=2.37), followed by human capital development (82.7% increase, d=2.54). Psychological well-being indicators demonstrated notable improvements in self-confidence (26.9%), life satisfaction (39.7%), and stress management (100%). Correlation analysis revealed mentorship quality as the strongest predictor of comprehensive empowerment (r=0.478, p<0.001). The research confirms the efficacy of integrating financial assistance with capacity-building initiatives, reinforcing theoretical models emphasizing holistic Islamic development. High participant satisfaction rates (92.5% rating ≥8/10) indicate program acceptance and sustainability potential. These findings strengthen strategies for achieving Sustainable Development Goals and provide evidence for effective zakat allocation policies. This research advances Islamic social finance methodology by demonstrating PSM's relevance in evaluating faith-based development interventions, establishing a robust framework for future impact assessments in Muslim-majority contexts.